POLYCYCLIC AROMATIC HYDROCARBONS (PAHS) IN SEAFOOD CAUGHT OFF IN NAPOLI GULF (ITALY) - R. Marrone; R. Mercogliano; G. Palma; C. Chirollo; G. Smaldone; A. Anastasio (Italian Journal of Food Safety, 2011)
Benzo(a)pyrene and other 12 polycyclic aromatic hydrocarbons (PAHs) were determined by high performance liquid chromatography (HPLC) with fluorescence detection in different seafoods (Merluccius merluccius, Arnoglossus laterna, Scomber japonicus, Eledone moschata and Penaeus kerathurus) collected along the coast of Napoli gulf (Italy). The results showed that Bap levels exceeded the limit fixed by EU Regulation 1881/2006 in several species and the concentrations of PAHs were higher in winter than in summer season. The presence of carcinogenic PAH in fish is dangerous to human health and should be seriously considered.